1997
DOI: 10.1007/s000110050536
|View full text |Cite
|
Sign up to set email alerts
|

Serial cytokine changes in peritoneal effluent and plasma during peritonitis in patients on continuous ambulatory peritoneal dialysis (CAPD)

Abstract: Secretion of IL-6 and IL-8 pro-inflammatory cytokines which are mainly synthesized in mesothelium cells is followed by the activation of lymphocytes, their infiltration and the production of T lymphocyte derived IL-2 and sIL-2R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…We have shown here that the peritoneal pool of CD14 + cells is not terminally differentiated since in vitro culture of these cells with standard polarizing conditions resulted in the generation of DC or macrophages. The interesting aspect of this finding is not that the peritoneal CD14 + population of PD patients can become DC after culture, as this has been shown previously in mice (14), but that they have a unique differentiation pathway as illustrated by the fact that these cells do not uniformly down-regulate CD14 expression as peripheral blood monocytes do during their differentiation to DC [41]. After 6 days of culture, peripheral blood monocytes are completely negative for CD14, while two populations of cells, one CD14 -/lo and another CD14 + , are clearly distinguishable after peritoneal cells are cultured with GM-CSF and IL-4.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We have shown here that the peritoneal pool of CD14 + cells is not terminally differentiated since in vitro culture of these cells with standard polarizing conditions resulted in the generation of DC or macrophages. The interesting aspect of this finding is not that the peritoneal CD14 + population of PD patients can become DC after culture, as this has been shown previously in mice (14), but that they have a unique differentiation pathway as illustrated by the fact that these cells do not uniformly down-regulate CD14 expression as peripheral blood monocytes do during their differentiation to DC [41]. After 6 days of culture, peripheral blood monocytes are completely negative for CD14, while two populations of cells, one CD14 -/lo and another CD14 + , are clearly distinguishable after peritoneal cells are cultured with GM-CSF and IL-4.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, we demonstrate that the entire peritoneal pool of CD14 + mononuclear cells have the capacity to differentiate into DC or macrophages in vitro , under appropriate conditions, indicating that these cells are not fully differentiated despite their location in peripheral tissues. These data provide a mechanistic explanation for the predominant Th1 environment observed during episodes of PD-related peritonitis [14,15].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…It has been reported that in CAPD patients, there was an active release of proinflammatory cytokines and growth factors through at least 6 weeks after apparent clinical remission of peritonitis [8]. It has also been shown that the levels of interleukin-6 and interleukin-8 in the PDF and plasma were significantly increased during peritonitis in patients on CAPD [9]. In cirrhotic patients with spontaneous bacterial peritonitis, it has been demonstrated that the plasma and ascitic fluid cytokine levels were significantly higher in those patients who developed renal impairment, suggesting that the inflammatory response to infection might be an important mechanism of renal impairment [10].…”
Section: Discussionmentioning
confidence: 99%
“…Stippled bars, GAPDH In this study we utilized IL-1 , TNFα, and IL-6 as the cytokine supplements because resident peritoneal cells, such as peritoneal macrophages, mesothelial cells, and fibroblasts, produce these cytokines in conditions of both acute and chronic inflammation. [13][14][15][16][17][18][19][20][21][22][23][24][25] For example, low but significant levels of IL-6 (81 pg/ml) in PDE were detected in peritonitis-free patients while 100-to 1000-fold IL-6 levels in PDE were shown in patients with staphylococcal peritonitis. 16 One important role of IL-6 is its anti-inflammatory Fig.…”
Section: Discussionmentioning
confidence: 99%